Glycan regulation of receptor functions - Taniguchi, Naoyuki (Henry Stewart Talks, 2012)
Review of cell surface glycoprotein receptors, Glucose transporters 2, Integrins, Epidermal growth factor receptor, Platelet Endothelial adhesion molecules, Transforming growth factor beta receptor, the common structure of these receptors, Production of N-glycans, N-glycans in disease: diabetes and COPD